Religion, class and culture : indigenous churches in South Africa, with special reference to Zionist-Apostolics - Kruss, Glenda (Department of Religious Studies, 2016)
Part one establishes the problematic of this primarily historical and theoretical work on indigenous churches in South Africa. The existing literature is surveyed, explanatory themes isolated and a critique of the dominant functionalist framework offered. A different theoretical framework - historical materialism - is proposed, in order to bring new insights into the explanation of indigenous churches. A periodisation of the South African social formation, and three corresponding forms of indigenous churches is proposed. Part two considers each of these in a schematic form. It is hypothesized that Ethiopian churches arose at the turn of the century in the Transvaal and Eastern Cape amongst the emerging African petit-bourgeoisie. They were the religious response to unequal incorporation in the developing capitalist social formation. An early form of Zionism, Zion City Churches, arose between the two World Wars, in a period of intense resistance to proletarianization. In each region they were shaped by the particular conditions and conflicts. An attempt is made to demonstrate that, in contrast, Zionist-Apostolics arose after World War II as a church of the black working class. Instead of explaining them in terms of acculturation, it is hypothesized that their healing form can be understood as an expression and a protest of the alienation of the black working class. As a religious-cultural innovation they succeed in subverting missionary hegemony and gaining control over the means of salvation, and in this way, of their own lives. Part three attempts to evaluate the contribution of a historical materialist analysis to understanding religion, and to isolate directions for future research.